2011
DOI: 10.1002/mnfr.201100105
|View full text |Cite
|
Sign up to set email alerts
|

Catechols in caffeic acid phenethyl ester are essential for inhibition of TNF‐mediated IP‐10 expression through NF‐κB‐dependent but HO‐1‐ and p38‐independent mechanisms in mouse intestinal epithelial cells

Abstract: This study reveals the structure-activity effects and anti-inflammatory potential of CAPE in the intestinal epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Therefore the finding that the anti-inflammatory properties of NOD rely on its redox activity was not surprising and compatible with published studies on polyphenols [55], [56]. Our data are also in line with a previously published study in which it was shown that catechols in caffeic acid phenethyl ester (CAPE) selectively inhibit NFκB target genes [17].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore the finding that the anti-inflammatory properties of NOD rely on its redox activity was not surprising and compatible with published studies on polyphenols [55], [56]. Our data are also in line with a previously published study in which it was shown that catechols in caffeic acid phenethyl ester (CAPE) selectively inhibit NFκB target genes [17].…”
Section: Discussionsupporting
confidence: 92%
“…While it has been unambiguously demonstrated that a number of polyphenols possess strong anti-inflammatory action, the underlying mechanism has been equivocally discussed in recent years. Although tested in different cells or cell lines obtained from different species, Nrf-2 mediated induction of HO-1 [15], [16], inhibition of NFκB [16], [17] and inhibition of PLA2 [13] all seems to be pivotal or contributing to the anti-inflammatory action.…”
Section: Introductionmentioning
confidence: 99%
“…The second mechanism could be triggered by the ability of the phenolic and flavonoid compounds like quercetin, CAPE, p -vanillin, p -coumaric acid, apigenin, and cinnamic acid, all of which are present in Chilean propolis, to neutralize oxidative species [38]. CAPE not only has been shown to inhibit activation of the nuclear transcription factor- (NF-) κ B signaling pathway [39], but also has strong ROS scavenging ability and activates NrF2 [40], thereby increasing an antioxidant stress response, which could in part explain the antioxidant effects observed in our study related to the increase in GSH and decrease of TBARS.…”
Section: Discussionmentioning
confidence: 99%
“…CAPE has been reported to have biological and pharmacological activities including antioxidant [9,10,11,12,13,14], anti-inflammatory [15,16], antiviral [17], anti-carcinogenic [18], and immunomodulating effects [6]. CAPE has demonstrated a potent antioxidant activity in previous studies using an in vitro model [9,10,11,12] as well as an in vivo animal model [13,14].…”
Section: Introductionmentioning
confidence: 99%